Respiratory Rehabilitation in COVID-19 Patients with Breathlessness: Literature Review - Hantoro, Agung Cuby; Soekiswati, Siti (Prosiding University Research Colloquium, 2022)
COVID-19 attacks the respiratory system caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). In Indonesia, as many as 32% of patients infected with SARS-CoV2 require ICU care. Patients are more likely to experience shortness of breath and death. Rehabilitation efforts in physical medicine specialists and medical rehabilitation are very important in improving respiratory function. The purpose of this study was to identify and analyze respiratory rehabilitation efforts in COVID-19 patients with shortness of breath. This research is a literature review type using the PRISMA method. Data were collected by browsing the Pubmed, Science Direct, and Google Scholar databases. The search results obtained 2,982 articles, then 11 articles were carried out with a literature review. In 11 articles analyzed, it was found that respiratory rehabilitation in COVID-19 patients can be carried out by administering oxygen therapy including (Nasal Canula (NC), endotracheal intubation, and tracheostomy). Breathing exercises include (pursed lip breathing, slow deep breathing, prone position, and regular breathing in a forward leaning position). Airway clearance techniques include (huffing, control cough, incentive spirometry, postural drainage, and sputum clearance) and passive exercises in bed. In conclusion, there is no better rehabilitation program. The rehabilitation program should be given as early as possible to achieve maximum stability in a shorter time.